Impacts of termites on selected soil physicochemical characteristics in the highlands of Southwest Ethiopia - Jembere, Abdeta; Berecha, Gezahegn; Tolossa, Alemayehu Regassa (published online, 2017)
Termites are reported to improve soil physicochemical properties thereby enhance soil fertility of their mound and foraging areas. Empirical study pertaining to these effects is missing in Southwest Ethiopia. For this study, soil samples affected by termite activities were collected at 1 m interval within 0–3 m distance from the base of six termite mounds on gently sloping and sloping land and analyzed for physicochemical parameters. The result of the analysis depicted that soil bulk density (1.38–1.15 g cm −3 ) and moisture content (21.1–9.9%) decreased with increased distance from the mound base. While clay content decreased with increased distance from the mound base from72.0% to 45.5%, sand and silt contents increased from 8.0% to 21.3% and 19.3% to 28.5%, respectively. PH (6.23), organic carbon (3.85%), total nitrogen (0.4%), cation exchange capacity CEC (30.43 cmol kg −1 ), exchangeable Ca (13.73 cmol kg −1 ), Mg (3.15 cmol kg −1 ), and PBS (56.8%) were higher on termite mounds. While, electrical conduc- tivity (0.03 dS m −1 –0.06 dS m −1 ), exchangeable K (0.52–0.93 cmol kg −1 ) and Na (0.02–0.03 cmol kg −1 ) showed increasing trend with the distance from the mound base. Our results indicated that termite mounds are important sinks of organic matter and mineral nutrients, and hence contribute to the enhancement of soil fertility. Thus, for subsistent farmers the uses of termite mounds as a fertilizer present an opportunity to improve agricultural production.
full text
Keywords: Termite; mound; slope; soil physical properties; soil chemical properties